2020
DOI: 10.1029/2019ea001022
|View full text |Cite
|
Sign up to set email alerts
|

Role of Westerly Jet in Torrential Rainfall During Monsoon Over Northern Pakistan

Abstract: Pakistan experiences several torrential rainfall events for many years due to interactive role of midlatitude atmospheric and warm moist monsoon circulations. Deadly events such as flash flooding, runoff, and mudslides may trigger by torrential rainfall events which pose significant threat to human assets. This study was undertaken based on three severe weather events (1988, 2010, and 2013) by using percentage departure to identify wet and dry years during the period 1985–2016, which occurred over northern Pak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…This implies that other contributing factors, such as co-occurrences of other modes of variability, compensate for or compound the impact of ENSO. Evidence suggests that jet stream meandering in the Northern Hemisphere may be one of the contributors (10)(11)(12)(13). On average, the subtropical westerly jet lies north of South Asia during the monsoon season (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…This implies that other contributing factors, such as co-occurrences of other modes of variability, compensate for or compound the impact of ENSO. Evidence suggests that jet stream meandering in the Northern Hemisphere may be one of the contributors (10)(11)(12)(13). On average, the subtropical westerly jet lies north of South Asia during the monsoon season (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The causes of the historical oods over Pakistan have been investigated in the literature [8][9][10][11][12][13][14][15][16][17][18][19] . On the synoptic scale, it is typically the South Asian monsoon low-pressure systems (LPSs) that often trigger deep convection and bring copious rainfall ahead and south of the storm center [8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…A large fraction of LPSs originate near the Bay of Bengal and penetrate deeper inland, where they play a crucial role in determining the amount and distribution of the summer rainfall over South Asia 11,12 . It has also been suggested that the upper-level divergence resulting from the extratropical troughs lying aloft northern Pakistan contributed to the extreme rainfall in 1988, 2010, and 2013 [13][14][15][16] . On the planetary scale, both Pakistan rainfall and its synoptic triggers are in uenced by the large-scale South Asian monsoon circulation, which is further regulated by the sea surface temperature (SST) anomalies over the tropical Paci c and Indian Oceans [e.g., El Niño-Southern Oscillation (ENSO), Indian Ocean Dipole (IOD)] [17][18][19] .…”
Section: Introductionmentioning
confidence: 99%
“…The synoptic conditions before the torrential rainfall of both cases indicated clear cyclonic circulations at 850 hPa as well as 500 hPa over the areas of heavy rain. These large‐scale circulations present over the study area contribute a lot to enhancing the convection (Bibi et al., 2020; Hassan et al., 2010; Ullah & Gao, 2012, 2013). Further, both events were simulated by using the WRF model to investigate the instability over rainfall areas.…”
Section: Introductionmentioning
confidence: 99%